Intelligent Vehicle Path Tracking and Stability Control Method Based on Extension Coordinated Control of AFS and DYC - Jiankang Lu; Renrui Wang; Changdong Wan (IEEE Access)
To enhance vehicle handling stability and address the limitations of active front steering (AFS) in maintaining stability when the tire lateral force becomes saturated, this paper designed a phase-plane-based extension coordinated control system by using direct yaw moment control (DYC). The vehicle driving state is divided into the classical domain, extension domain and non-domain in the extension set, and the correlation function is solved using the extension theory. The value of the correlation function determines the range of the vehicle domain and the control mode. When the vehicle is in the classical domain, the AFS control method alone improves the path-tracking accuracy. When the vehicle is in the extended domain, the AFS and DYC coordinated control method is adopted. When the vehicle is in the non-domain, DYC is used alone to improve stability. The coordination weights between controllers are determined by the correlation function. The simulation results show that the maximum tracking error under double lane change and lane changing conditions is reduced by 27.59% and 55.56%, respectively.